The Impact of Inflation, Interest Rates, Exchange Rates on Stock Prices in the LQ-45 stock index - ZAINUDDIN, Fatlina; SUWANDA, Suwanda; SYAKILA, Fatika; JUMRIANI, Jumriani (PT Keberlanjutan Strategis Indonesia, 2024)
The primary objective of investment is to enhance wealth, satisfy future requirements and achieve prosperity through a frugal lifestyle. Stocks represent one of the most popular investment instruments. The capital market offers a range of stock indices, including the LQ45. The LQ45 index was selected due to its composition of leading stocks with high liquidity and favorable performance on the Indonesia Stock Exchange (IDX). This study aims to analyze the effect of macroeconomic factors, namely Inflation, interest rates, and exchange rates, on stock prices in the LQ45 index. The study employs a quantitative approach, utilizing secondary data obtained from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the years 2022 to 2023. The data used in this study are quantitative data obtained from secondary sources. The data were then analyzed using multiple linear regression methods, t-tests, and descriptive analysis. The findings indicate that Inflation, interest rates, and exchange rates exert a notable influence on stock prices within the LQ45 index.